Implikasi Pemahaman Bahasa Cinta bagi Relasi Suami Istri - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
Effective communication is actually not based on whether many or a few messages are communicated by both the husband and wife, but lies in the reasons and the delivery procedures. It is rare for a married couple and a family to have the same language of love or the main language of love. Married couples have a tendency to use their respective primary love languages, and in the end, husband and wife often get confused if they don't even understand what their husband or wife actually communicates. This is the crux of the problem. The method used in writing this journal is an analysis based on a bibliography so as to find the concept of the language of love for husband and wife relationships.